2012
DOI: 10.1007/s13337-012-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Molecular Genotyping of Group A Rotaviruses in Iranian Children

Abstract: Rotavirus is the leading cause of acute gastroenteritis in worldwide young children. Effective vaccines to prevent rotavirus infection are currently available, although their clinical use is still limited, and rotavirus still causes many episodes of infantile gastroenteritis, mainly during the winter season. The aim of this study was to evaluate the prevalence of rotavirus infection in children aged \5-years-old who were hospitalised for gastroenteritis. One hundred and sixty-three stool samples from hospitali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…We reviewed 145 articles/abstracts to select a total of 28 that met the inclusion criteria of the current review (Figure 1). The selected studies covered Bahrain (10), Egypt (11,12), Islamic Republic of Iran (13)(14)(15)(16)(17)(18)(19)(20)(21), Iraq (22,23), Jordan (24,25), Libya (26), Morocco (27)(28)(29), Saudi Arabia (30-32), Tunisia (33), Turkey (34,35), United Arab Emirates (UAE) (36), and Yemen (37). All studies from Algeria, Jordan, Leb-anon, Oman, Palestine, and Qatar were excluded because these did not meet our inclusion criteria whereas no studies were available from Kuwait and the Syrian Arab Republic.…”
Section: Studies Selected For Reviewmentioning
confidence: 99%
“…We reviewed 145 articles/abstracts to select a total of 28 that met the inclusion criteria of the current review (Figure 1). The selected studies covered Bahrain (10), Egypt (11,12), Islamic Republic of Iran (13)(14)(15)(16)(17)(18)(19)(20)(21), Iraq (22,23), Jordan (24,25), Libya (26), Morocco (27)(28)(29), Saudi Arabia (30-32), Tunisia (33), Turkey (34,35), United Arab Emirates (UAE) (36), and Yemen (37). All studies from Algeria, Jordan, Leb-anon, Oman, Palestine, and Qatar were excluded because these did not meet our inclusion criteria whereas no studies were available from Kuwait and the Syrian Arab Republic.…”
Section: Studies Selected For Reviewmentioning
confidence: 99%
“…Although G2 and G3 are among the most prevalent rotavirus genotypes worldwide (Fang et al, 2005;Dey et al, 2009;Wang et al, 2009;Jere et al, 2011), Kargar et al 2939 nonetheless this strains were not detected in this study. In recent years G4 strain has been detected at relatively high frequency from Germany (Van Damme et al, 2007), Italy (Annarita et al, 2010), South Korea (Shim et al, 2010) and some regions of Iran (Khalili et al, 2004;Eesteghamati et al, 2009;Kargar and Akbarizadeh, 2011). However, G4 was detected only in 2.27% of all children with rotavirus gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, non-typeable genotypes were present in 40.91% of all the rotavirus positive fecal samples. These rotavirus strains have been detected only rarely in other investigations (Pun et al, 2007;Eesteghamati et al, 2009;Annarita et al, 2010;Kargar and Akbarizadeh, 2011). Non-typeable samples might be the result of a false-positive EIA, the presence of novel strains, the nonuse of specific primers for rare genotypes such as G5, G6, G11 or the failure in RT-PCR technique (WHO, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The search was performed on 2 databases 1) the Pubmed and 2) the IranMedex (a database indexing published studies in Farsi language). The literature search identified; 1) 2 major community surveys that reported the prevalence of all cause diarrhea, 2) one community based study that reported proportion of cause specific rotavirus diarrhea among outpatients with all cause diarrhea, 3) 9 hospital based studies [25][26][27][28][29][30][31][32][33][34] that reported the proportion of cause specific rotavirus diarrhea among the hospitalized all cause diarrheal patients. The two community surveys included; a World Bank funded research that measured prevalence of diarrhea in a sample of 5 cities throughout the country, 35 and the other one reported the result of the Multiple-Indicator Demographic and Health Survey (MIDHS) performed in 2010.…”
Section: The Incidencementioning
confidence: 99%